OFFLINE BUT CONNECTED: PROFESSIONAL EDUCATION FOR PRE-SERVICE ENGLISH TEACHERS’ VIEWS ON LEARNING MANAGEMENT SYSTEM UTILIZATION FOR TASKSUBMISSION - Nisa, Indah Khoirun (International Conference on Humanity Education and Society (ICHES), 2024)
To improve the quality of education in Indonesia, government issued a new breakthrough, namely the new model of pre-service teacher professional education (PPG). Teacher Professional Education Program itself is an educational program held to prepare undergraduate graduates. Students Of the New Model Pre-service PPG do offline learning and submit assessments in Learning Management System (LMS). Learning Management System or LMS is A Learning Management System is a web- based software application that is designed to handle learning content, student interaction, assessment tools and reports of learning progress and student activities. In LMS there is a learning line. The learning line exists in LMS used at New Model Pre-service PPG is MERDERKA. MERDEKA is acronym of Mulai dari diri, Eksplorasi konsep, Ruang kolaborasi, Demonstrasi kontekstual, Elaborasi pemahaman, Koneksi antar materi and Aksi nyata. This research uses qualitative approach while qualitative descriptive is used as a method. The researcher used observation and interview to collect the data. Based on the research which has been conducted, the main result is Learning Management system could facilitate assessment submission process by many features. Various form of assignment files could be uploaded in LMS easily. This is why Learning Management System is quite effective to be used for assessment submission with good internet connection.